2009
DOI: 10.1074/jbc.m109.015362
|View full text |Cite
|
Sign up to set email alerts
|

Epac Activates the Small G Proteins Rap1 and Rab3A to Achieve Exocytosis

Abstract: Exocytosis of the acrosome (the acrosome reaction) relies on cAMP production, assembly of a proteinaceous fusion machinery, calcium influx from the extracellular medium, and mobilization from inositol 1,4,5-trisphosphate-sensitive intracellular stores. Addition of cAMP to human sperm suspensions bypasses some of these requirements and elicits exocytosis in a protein kinase A-and extracellular calcium-independent manner. The relevant cAMP target is Epac, a guanine nucleotide exchange factor for the small GTPase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
124
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 90 publications
(139 citation statements)
references
References 97 publications
15
124
0
Order By: Relevance
“…We previously reported that sperm contain a GEF activity that exchanges GDP for GTP on Rab3A when challenged with calcium or 8-pCPT-2′-O-Me-cAMP (35,47). We conducted those earlier experiments in SLO-permeabilized human sperm, but because we performed the Rab27 pull-down experiments reported in this paper with nonpermeabilized sperm, we wished to verify the Rab3A data under the same conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that sperm contain a GEF activity that exchanges GDP for GTP on Rab3A when challenged with calcium or 8-pCPT-2′-O-Me-cAMP (35,47). We conducted those earlier experiments in SLO-permeabilized human sperm, but because we performed the Rab27 pull-down experiments reported in this paper with nonpermeabilized sperm, we wished to verify the Rab3A data under the same conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Because Rab27A and Rab27B have very similar electrophoretic mobility, and because the anti-Rab27 antibody that we used is supposed to recognize both isoforms, we cannot distinguish which of the two is present in sperm. By introducing specific anti-Rab antibodies that sequester the endogenous proteins or recombinant cassettes that selectively bind the active forms into SLO-permeabilized human sperm, we found that both Rab3A (32,35) (Fig. 4 and Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated previously, acrosomal exocytosis is organized as a bifurcated pathway, with two separate limbs that diverge downstream of cAMP/Epac (28). The end point of one branch is the mobilization of intracellular calcium from internal stores through the activation of PLC via Rap, whereas the other branch (Rab3A-SNAREs) assembles the fusion protein machinery so that the outer acrosomal and plasma membranes become physically connected (protein branch).…”
Section: Arf6 Promotes Calcium-regulated Exocytosismentioning
confidence: 99%
“…During exocytosis, there are some parallel and concomitant steps necessary to achieve AR that occurs thereafter. This signaling cascade involves preparation of the fusion machinery that includes SNAREs (21,22), ␣-SNAP/NSF (23), synaptotagmin (24), Rab3A (25,26), and exchange protein directly activated by cAMP (Epac), a GEF protein that links cAMP and intracellular calcium signaling (27,28). It has been proposed that a soluble adenylyl cyclase is activated by a sustained increase in intracellular calcium, resulting in a cAMP increase that activates Epac.…”
mentioning
confidence: 99%